A mathematical model for estimating effective stimulated reservoir volume - Ibrahim, A.U. (Springer Science and Business Media Deutschland GmbH, 2021)
This study presents a model application for the evaluation of Effective Stimulated Reservoir Volume (ESRV) in shale gas reservoirs. This current model is faster, cheaper, and readily available for estimating ESRV compared to previously published models. Key controlling parameters for efficient ESRV modeling, including geomechanical parameters and time, are considered for the model development. The model was validated for both single and multi-stage fractured reservoirs. For the single fractured reservoir, an ESRV of 3.07 Ã 106 ft3 was estimated against 3.99 Ã 106 ft3 of ESRV-FEM field data. Whereas, 7.00 Ã 109 ft3 ESRV was estimated from the multi-stage fractured reservoir against 7.90 Ã 109 ft3 of fractal-based model results. Stress dependence, time dependence, and permeability dependence of shale gas reservoirs are found to be essential parameters for the successful calculation of ESRV in reservoirs. An ESRV determined using this method can obtain the estimated ultimate recovery, propped volume, optimal fracture length, and spacing in fractured shale gas reservoirs. Â© 2021, The Author(s).